Snake - A Loop in Time - Potrebica, Hrvoje (Array, 1998)
Snake is one of the strongest and, perhaps, the oldest symbol in human history. It can be found in the deepest level of almost every Creation myth. We find it on all springs of life spiritual and corporal. It is the oldest god and mythical forefather of gods and men. It is the reanimating and inspiring force doctor and medicine man, wisdom and magic intertwined. It had healing power over body and spirit, but it also carried terrible and swift death. That is why it was revered and worshiped, but at the same time also feared and hated. It has always been either archetype of Evil, or symbol of Good. It has always been king of the underworld, messenger of the dead that emerges from the darkness to the ground to communicate its dark message. But it also rode the clouds and ruled the sky. It has come a long way from Quetzalcoatl of Aztecs and Toltecs, redeemer of men, that, astonishingly similar to Christ, sacrifices itself to save the humanity, to the Evil Tempter from Genesis, that offers knowledge in exchange for peace of mind. In between stands the goddess of wisdom, Athena, still holding at her hand, or at her breast, snake that gave birth to gods, nations and kings. What is than its real character? Perhaps it is all Uruboros, a snake biting its own tail, eternal movement, recreation and continuity; a circle connecting chthonic with celestial, earth and heavens, good and evil, darkness and light, yin and yang. Perhaps it is a loop in time, with the world in the middle.